Structural and functional properties of a magnesium transporter of the SLC11/NRAMP family - Karthik Ramanadane; Monique S Straub; Raimund Dutzler; Cristina Manatschal (eLife, 2022)
Members of the ubiquitous SLC11/NRAMP family catalyze the uptake of divalent transition metal ions into cells. They have evolved to efficiently select these trace elements from a large pool of Ca2+ and Mg2+, which are both orders of magnitude more abundant, and to concentrate them in the cytoplasm aided by the cotransport of H+ serving as energy source. In the present study, we have characterized a member of a distant clade of the family found in prokaryotes, termed NRMTs, that were proposed to function as transporters of Mg2+. The protein transports Mg2+ and Mn2+ but not Ca2+ by a mechanism that is not coupled to H+. Structures determined by cryo-EM and X-ray crystallography revealed a generally similar protein architecture compared to classical NRAMPs, with a restructured ion binding site whose increased volume provides suitable interactions with ions that likely have retained much of their hydration shell.